The floods in Greece: the case of Mandra in Attica - Soulios, Georgios; Stournaras, Georgios; Nikas, Konstantinos; Mattas, Christos (Bulletin of the Geological Society of Greece, 2018)
Floods are one of the most common natural disasters and are extremely dangerous in a global range since they can cause extensive damage to properties or losses in human lives. According to the opinion of many expert scientists, climate change has led to the increase of flooding phenomena over the last years worldwide, as well as in Greece. The aim of this paper is to examine the flooding event that occurred in Mandra area, Attica (Greece) on 14-15 November of 2017. The peak discharge of the Agia Ekaterini and Soures streams was calculated using the rational method (Giandotti) for return periods equal to 10, 100 and 1000 years. The stream characteristics were studied and their behavior during the flood was investigated. Many of the impacts were attributed to the human intervention in the streambeds.